Ecological network analysis of solar photovoltaic power generation systems. (20th June 2019) - Briese, Emily; Piezer, Kayla; Celik, Ilke; Apul, Defne
Abstract: Ecological network analysis (ENA) is emerging as a powerful tool for studying complex technological systems and can reveal information not captured by life cycle assessment (LCA). In this study, we developed an ENA based on the material, energy, and water life cycle inventory of CdTe photovoltaic (PV) modules. We defined one ecological (sun) and eight technological (manufacturing, construction, power grid, solar energy, fuel, water, recycling and waste treatment, and dissipation) network compartments. We studied the interactions of these compartments using throughflow analysis (TA), network utility analysis (NUA), network control analysis (NCA), and network stability analysis (NSA). The TA revealed that total throughflow of the system (TST), or quantified total size of the system is for producing 1 kWh of electricity from solar power is 604 kWh. The NUA assessed the symbiotic relationships within the system and revealed that both quantitative and qualitative beneficial relationships between compartments are prominent. Also, mutualism and synergism indexes were calculated as 2.4 and 7.0, respectively, indicating that most of the system compartments are gaining energy; thus, the system is flexible and preferable for industries when the system compartments are increasing their involvement and cycling within the system. The NCA results indicated that most of the compartments have control over the dissipation compartment, which suggested that large amounts of energy are lost in those compartments. Also, not surprisingly, almost all the compartments were dependent on fuel and water. Our NSA results showed that the current solar energy system lacks systematic diversity and resilience; it lacks the ability to return to the original state when the system is stressed. However, the main reason for these results is the low conversion efficiency of photonic energy to electricity. The same issue would apply to all other engineered power generation systems as well due to low fundamental limits of energy conversion. Graphical abstract: Image 1 Highlights: An energy-water-material nexus framework for PV systems was proposed. The symbiotic relationships within the system are prominently beneficial. Almost all the compartments are dependent on the fuel and water compartments. The PV systems lack systematic diversity due to low power conversion efficiency.